Suicidal process - Keturakis, V. (Psichologija, 1995)
This paper aims to show on the basis of various theoretical models that suicide is a process of multifactorial nature. Psychoanalytic approach has changed over the years and now it is represented by H. Henseler's narcissistic theory of suicide, which deals with the collapse of the regulation of self-esteem preceding the suicidal behaviour. Cognitive model adds that the chain of cognitive misbehaviour leads to suicidal fantasies. Social causation of suicide is presented in E. Diurkheim's sociological study of the phenomenon which deals with suicidogenic tendencies in society: egoism, or the loss of cohesiveness in society; altruism, or over integration in social group, and anomie, or the collapse of regulative norms. In the last part of this paper it is said that, if suicide is multifactorial phenomenon, as well as a process, so the aid can be provided intervening it with the hope for success.
Keywords: suicidar process; suicide; origin of suicide